Electrochemical performance of aqueous hybrid supercapacitor based on LiFePO4/Si/graphene composite - Wan, N.W.K.; Lim, H.N.; Ibrahim, I.; Huang, N.M.; Foo, C.Y.; Jiang, Z.T. (Elsevier, 2022)
Aqueous hybrid supercapacitors (HS) are a viable alternative to achieve low-cost, environmentally friendly, and safer energy storage technologies. Herein, lithium iron phosphate modified silicon and graphene derivatives (LFP/Si/graphene) are constructed as the cathode, and graphene nanoplatelets (GNPs) as the anode for an aqueous HS. The incorporation of GNPs and reduced graphene oxide (rGO), which is the source of graphene derivatives (graphene) in the composite, has played the role of an electronic conductivity enhancer for LFP/Si structure in the framework structure of the rGO film. Therefore, Si is able to perform its role effectively in avoiding surface instability issues and preventing the side reaction of LFP in aqueous electrolyte. The electrochemical performance is evaluated in a 1 M Li2SO4 aqueous electrolyte that has been thoroughly deaerated with high-purified argon (Ar) gas to remove any dissolved oxygen that might interfere with the analysis. The Ar blanketing in the electrolyte intensified the electrochemical performance by 60 as compared to the Ar-free electrolyte. The coated LFP by 0.5 w/w Si with incorporation of graphene (LFP/Si0.5/graphene) for electronic conductivity enhancement in Swagelok-type cells has an exceptional specific capacitance of 272.6 F/g and a highly improved cycle life, which shows 87.2 capacitance retention after 5200 cycles. Moreover, a different assembly of a close-to-current commercial format of roll-type cell is also studied, and it exhibits slightly higher in specific capacitance of 301.3 F/g with energy and power density of 35.62 Wh kgˆ’1 with 922.53 W kgˆ’1, respectively. Therefore, both cell configurations using LFP/Si0.5/graphene display promising applications of the HS, which have the potential to slowly build themselves into a vital role in hybrid-electric technology.